Bone marrow cells as precursors of the tumor stroma - Worthley, Daniel L. (2013)
Cancer is a systemic disease. Local and distant factors conspire to promote or inhibit tumorigenesis. The bone marrow is one important source of tumor promoting cells. These include the important mature and immature hematopoietic cells as well as circulating mesenchymal progenitors. Recruited bone marrow cells influence carcinogenesis at the primary site, within the lymphoreticular system and even presage metastasis through their recruitment to distant organs. In this review we focus on the origins and contribution of cancer-associated fibroblasts in tumorigenesis. Mesenchymal cells present an important opportunity for targeted cancer prevention and therapy.